2018
DOI: 10.3892/ijo.2018.4664
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt modulator ICG‑001 mediates the inhibition of nasopharyngeal carcinoma cell migration in vitro via the miR‑150/CD44 axis

Abstract: The Wnt modulator ICG-001 mediates the inhibition of The Wnt modulator ICG 001 mediates the inhibition of nasopharyngeal carcinoma cell migration in vitro via the miR-150/ nasopharyngeal carcinoma cell migration in vitro via the miR 150/ CD44 axis CD44 axis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…However, the regulation of expression and also the biological actions of EVI1 in NPC cells are still unknown. We have previously demonstrated that the small specific molecule CBP/β-catenin antagonist ICG-001 can inhibit the migration and growth of CSC-enriched NPC tumor spheres via the miRNA-145/SOX2 (SRY-Box Transcription Factor 2) axis [22] and miR-150/CD44 axis [23]. In the present study, we further examined the underlying antitumor mechanisms of ICG-001 in NPC cells.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…However, the regulation of expression and also the biological actions of EVI1 in NPC cells are still unknown. We have previously demonstrated that the small specific molecule CBP/β-catenin antagonist ICG-001 can inhibit the migration and growth of CSC-enriched NPC tumor spheres via the miRNA-145/SOX2 (SRY-Box Transcription Factor 2) axis [22] and miR-150/CD44 axis [23]. In the present study, we further examined the underlying antitumor mechanisms of ICG-001 in NPC cells.…”
Section: Introductionmentioning
confidence: 84%
“…Apart from the miR-449a, we have previously demonstrated that ICG-001 could also inhibit the growth of CSC-enriched NPC tumor spheroids via miR-145/SOX2 axis [22] and the NPC cell migration via miR-150/CD44 axis [23]. Figure 8 summarizes the hypothetical mode of action of ICG-001 on NPC cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations